DNA Immunization with the Cysteine-Rich Interdomain Region 1 of the Plasmodium falciparum Variant Antigen Elicits Limited Cross-Reactive Antibody Responses - Baruch, Dror I. (American Society for Microbiology, 2003)
The variant surface antigens of Plasmodium falciparum are an important component of naturally acquired immunity and an important vaccine target. However, these proteins appear to elicit primarily variant-specific antibodies. We tested if naked DNA immunization can elicit more cross-reactive antibody responses and allow simultaneous immunization with several variant constructs. Mice immunized with plasmid DNA expressing variant cysteine-rich interdomain region 1 (CIDR1) domains of the P. falciparum erythrocyte membrane protein 1 (PfEMP1) developed antibodies that were reactive to the corresponding PfEMP1s as measured by an enzyme-linked immunosorbent assay, flow cytometry, and agglutination of parasitized erythrocytes (PEs). We observed some cross-reactive immune responses; for example, sera from mice immunized with one domain agglutinated PEs of various lines and recognized heterologous domains expressed on the surface of Chinese hamster ovary (CHO) cells. We found no significant antigenic competition when animals were immunized with a mixture of plasmids or immunized sequentially with individual constructs. Moreover, mixed or sequential immunizations resulted in greater cross-reactive agglutination responses than immunization with a single domain. Recombinant protein (Sc y179) immunization after priming with DNA (prime-boost regimen) increased antibody titers to the homologous domain substantially but seemed to diminish the cross-reactive responses somewhat. The titer of agglutinating antibodies was previously shown to correlate with protection. Surprisingly, the agglutination titers of sera from DNA immunization were high, similar to those of pooled human hyperimmune sera. These sera also appeared to give limited low-titer variant transcending agglutination. Thus, DNA immunization appears to be a very useful tool for developing variant antigen vaccines.